SIRT6 Reduces Rheumatoid Arthritis Injury by Inhibiting MyD88-ERK Signaling Pathway - Yu, Xiaolong; Jin, Zihan; Raza, Faisal; Zhang, Ping; Wu, Jiabiao; Ren, Min; Wang, Jiapeng; Xi, Jing (Frontiers in bioscience (Landmark. Print), 2024)
Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by destruction of synovial joints, abnormal immune responses and chronic inflammatory manifestations, which seriously affects patients’ well-being. We explored this study to ascertain the effect and mechanism of silent information regulator 6 (SIRT6) on RA. Methods: Genes of RA patients and normal volunteers were analyzed using Gene Expression Omnibus (GEO), Kyoto-Encyclopedia of Genes and Genomes (KEGG) and Disconet databases. Serum samples of RA patients and normal subjects were collected before detection of myeloid differentiation factor-88 (MyD88)-extracellular signal-regulated kinase (ERK) pathway proteins expression with Western blot. In vitro RA fibroblast-like synoviocytes (FLS) cell model (RA-FLS) was established by treating RSC-364 with recombinant rat IL-1β (10 ng/mL) after which SIRT6 and MyD88 adenoviruses treatment was carried out. The enzyme linked immunoassay (ELISA), real time polymerase chain reaction (RT-PCR) and Western blot were respectively used to measure inflammatory factors, related messenger ribonucleic acid (mRNA) and protein expressions. Also, we constructed RA rat model with bovine type II collagen (BIIC) and complete Freund’s adjuvant, before treatment with SIRT6 and MyD88 adenoviruses. Results: Low expression of SIRT6 gene were detected in RA patients. Also, levels of MyD88, ERK and phosphorylated extracellular signal-regulated protein kinase (p-ERK) protein expressions in RA patients were increased, whilst that of SIRT6 protein decreased. Compared to FLS cells in Control group, inflammatory factors levels of rats in Model batch increased significantly. SIRT6 adenovirus treatment potentially and significantly inhibited inflammation including suppression of increased inflammatory factors induced by MyD88. In comparison with FLS cells in Control group, Model batch cells’ MyD88, interleukin (IL)-1β, IL-21, IL-22, IL-6, IL-17, tumor necrosis factor-alpha (TNF-α) and monocyte chemo-attractant protein-1 (MCP-1) mRNA expressions increased but SIRT6 gene treatment could reduce mRNA expression of the aforesaid factors, even after MyD88 adenovirus treatment. Besides, overpressed SIRT6 negatively regulated levels of MyD88, ERK and p-ERK proteins expressions. SIRT6 demonstrated anti-RA effect by regulating MyD88-ERK pathway and inhibiting inflammatory response in RA rats. Conclusions: SIRT6 could potentially inhibit the inflammatory response of RA via a regulatory mechanism mainly relating to MyD88-ERK signal pathway. Thus, SIRT6 and its agonists may serve as new targets for developing drugs that can potentially treat RA.